Startup communities building an entrepreneurial ecosystem in your city - Feld, Brad (Hoboken, New Jersey John Wiley & Sons, Inc., 2012)
"'Startup Communities' documents the buzz, strategy, long-term perspective, and dynamics of building communities of entrepreneurs who can feed off of each other's talent, creativity, and support. Based on more than twenty years of Boulder-based entrepreneur turned-venture capitalist Brad Feld's experience in the field--as well as contributions from other innovative startup communities--this reliable resource skillfully explores what it takes to create an entrepreneurial community in any city, at any time. Along the way, it offers valuable insights into increasing the breadth and depth of the entrepreneurial ecosystem by multiplying connections among entrepreneurs and mentors, improving access to entrepreneurial education, and much more"--Publisher description.
Includes index.
Keywords: Entrepreneurship; New business enterprises -- Environmental aspects; Communities -- Social aspects